2018
DOI: 10.5433/1679-4842.2017v20n1p119
|View full text |Cite
|
Sign up to set email alerts
|

Condições socioeconômicas e saúde das famílias portadoras de anemia falciforme

Abstract: A anemia falciforme é doença hereditária caracterizada pela alteração dos glóbulos vermelhos do sangue, tornando-os parecidos com uma meia lua. A pesquisa teve como objetivo mostrar as condiçoes socioeconômicas das famílias com doença falciforme moradoras na comunidade quilombola Negros do Riacho, no município de Currais Novos, Rio Grande do Norte. Adotou-se uma abordagem qualiquantitativa. Os dados foram coletados através de entrevistas semiestruturadas realizadas no domicílio dos participantes, após a assina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…On the other hand, a study conducted in Rio Grande do Norte with approximately 100 people revealed that (72.2%) of the participants received some type of social benefit, however, most referred to the benefit as the only source of family income. 10,11 With regard to education, it is noteworthy that none of the participants were in the school year according to their age and failure was more frequent in people aged 18 or older. Consistent data was found in the literature, which points out that (38.3%) of adult sickle cell patients in Brazil had low education, a situation that will possibly reflect in their lives as adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a study conducted in Rio Grande do Norte with approximately 100 people revealed that (72.2%) of the participants received some type of social benefit, however, most referred to the benefit as the only source of family income. 10,11 With regard to education, it is noteworthy that none of the participants were in the school year according to their age and failure was more frequent in people aged 18 or older. Consistent data was found in the literature, which points out that (38.3%) of adult sickle cell patients in Brazil had low education, a situation that will possibly reflect in their lives as adults.…”
Section: Resultsmentioning
confidence: 99%
“…The work, in general, contributes decisively to their insertion in society, helping them in maintaining their health. 11,15 Regarding the profession, a study found that (72.2%) have their family income derived from some type of social benefit, of the (38.3%) who worked, only (5.5%) were formal jobs. Proving that sickle cell anemia is a chronic disease that causes limitation from the socioeconomic point of view.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16 As an alternative to this adversity, the guardians are instructed to boil water as recommended by the Ministry of Health. 17,18 It was identified that a minority of patients reported some adverse event related to the use of SCD medications, and this is due to the fact that this information was spontaneously reported. Common adverse reactions caused by phenoxymethylpenicillin are diarrhea, epigastric discomfort, nausea, vomiting; and those caused by folic acid are bad taste in the mouth, loss of appetite and nausea.…”
Section: Reasons For Inadequacy To the Guidelines Frequency N (%) N=35mentioning
confidence: 99%